Effectiveness of a 6-week core muscle high-intensity interval training program on core stability and power in swimmers - Ashira Hiruntrakul; Tanapol Kaewwong; Surumpa Charoensuk Kaewwong; Parichat Rirermkul; Narong Jomkokkruad; Charee - Jansupom (Human Movement)
Purpose This study aimed to investigate the effectiveness of core muscle high-intensity interval training on core stability and power in swimmers.